TINJAUAN FILOSOFIS TENTANG KONSEP HUMANISME SERTA IMPLIKASINYA DALAM LEMBAGA PENDIDIKAN ISLAM INTEGRAL - Sutikno; Alaika, Alaika M. Bagus Kurnia PS; Anggraeni, Arista; Dahlia, Dahlia Damayanti Sholikhah; 'Izzah, Nur ‘Izzah Maulidiya (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
Humanism is a philosophical concept that places a high value on the inherent nature, boundaries, and natural tendencies of human beings, with humans as the central object. Humanism has significant implications in the context of integral Islamic educational institutions because it emphasizes human values, individual potential enhancement, and respect for human dignity. This research aims to provide a comprehensive insight into the relevance and challenges of introducing a humanistic approach in the context of integral religious education, which can help enrich the understanding and implementation of these concepts in Islamic religious education practice. The research method used is a literature review. The results show significant implications of the concept of humanism on integral Islamic education, focusing on the spiritual, intellectual, moral, and social aspects.